A Survey on the Reading Habit of Indonesian Preservice EFL Teachers - Siti Aisah; Ana Ahsana El-Sulukiyyah; Rasyidah Nur Aisyah (Universitas Islam Negeri (UIN) Mataram, 2019)
Reading is a useful activity to get information which can expand students’ knowledge. This research is aims to investigate pre-service EFL teachers’ reading habit at STKIP PGRI Pasuruan. This survey research collected data from 130 pre-service EFL students who were randomly selected majoring in English and Education as the respondents. Questionnaires was distributed to collect the information regarding their reading habit,and were triangulated through observation. The statistical evidence showed that the student teachers’ interest and frequency of reading as well as their reading habit were poor. The main purpose of reading for the students, the majority of whom download the reading resources from the internet, was to gain knowledge. Most of the students preferred readings from websites and printed books.